Inhibiting N-acyl-homoserine lactone synthesis and quenching Pseudomonas quinolone quorum sensing to attenuate virulence - Chan, Kok-Gan; Liu, Yi-Chia; Chang, Chien-Yi (Frontiers in Microbiology, 2015)
Bacteria sense their own population size, tune the expression of responding genes and behave accordingly to environmental stimuli by secreting signalling molecules. This phenomenon is termed as quorum sensing (QS). By exogenously manipulating the signal transduction bacterial population behaviours could be controlled, which may be done through quorum quenching (QQ). QS related regulatory networks have been proven their involvement in regulating many virulence determinants in pathogenic bacteria in the course of infections. Interfering with QS signalling system could be a novel strategy against bacterial infections and therefore requires more understanding of their fundamental mechanisms. Here we review the development of studies specifically on the inhibition of production of N-acyl-homoserine lactone (AHL), a common proteobacterial QS signal. The opportunistic pathogen, Pseudomonas aeruginosa, equips the alkylquinolone (AQ)-mediated QS which also plays crucial roles in its pathogenicity. The studies in QQ targeting on alkylquinolone are also discussed.